2019
DOI: 10.1186/s12903-019-0969-0
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the anatomical relationship between the maxillary molars and the sinus floor in a Chinese population using cone-beam computed tomography

Abstract: Background: The anatomical relationship between the root apices of maxillary molars and the maxillary sinus floor (MSF) is important for the treatment of dental implantations and endodontic procedures. In this study, the detailed anatomical relationships between the root apices of maxillary molars and the MSF were studied in a Chinese population using CBCT. Methods: We collected the CBCT data files of patients who visited the stomatology outpatient clinic in Shanghai Fifth People's Hospital, Fudan University f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
15
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 26 publications
4
15
0
2
Order By: Relevance
“…Shokri et al 34 reported that palatal root protrusion of maxillary molars was more common, and other studies reported that buccal root protrusion was more frequent. 24,25,33 In this study, buccal protrusion (B3P0, B3P1, B3P2) was more common than palatal root protrusion (B2P3) ( Table 5).…”
Section: Discussionmentioning
confidence: 64%
See 2 more Smart Citations
“…Shokri et al 34 reported that palatal root protrusion of maxillary molars was more common, and other studies reported that buccal root protrusion was more frequent. 24,25,33 In this study, buccal protrusion (B3P0, B3P1, B3P2) was more common than palatal root protrusion (B2P3) ( Table 5).…”
Section: Discussionmentioning
confidence: 64%
“…Many studies have reported that the type 0 relationship was most commonly observed. 20 22 23 25 28 32 Other studies showed that type 0 was most frequently observed in premolars and type 3 in molars. 16 18 19 26 34 Differences in reported sinus-root relationships might be due to ethnicity or methodology.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Zhang et al [28] studied the sinus-root relation in the Chinese population on a total of 800 right and left first and second molars using CBCT images without mentioning the employed software. They nearly agreed with the current study in the percenatge of the roots contacting the sinus floor where they reported 21.75% and this study reported 23.4%.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies were concerned with analyzing the sinus-root relation in different populations including the Chinese [9,28], Iranian [11,26], Brazilian [29,30], Bulgarian [25], and Saudi Arabian [14] populations. The aim of this study is to assess the relationship between the roots of the maxillary molars and MSF in a sample of the Egyptian population-that was not involved in any previous study-using CBCT.…”
Section: Introductionmentioning
confidence: 99%